Inverse Association of Telomere Length With Liver Disease and Mortality in the US Population. Issue 2 (28th August 2021) - Rattan, Puru; Penrice, Daniel D.; Ahn, Joseph C.; Ferrer, Alejandro; Patnaik, Mrinal; Shah, Vijay H.; Kamath, Patrick S.; Mangaonkar, Abhishek A.; Simonetto, Douglas A.
Abstract : Physiologic aging leads to attrition of telomeres and replicative senescence. An acceleration of this process has been hypothesized in the progression of chronic liver disease. We sought to examine the association of telomere length (TL) with liver disease and its impact on mortality risk. A cohort of 7, 072 adults with leukocyte TL measurements from the National Health and Nutrition Examination Survey 1999‐2002 with mortality follow‐up through 2015 was analyzed. Liver disease was defined by aminotransferase levels and classified into etiology‐based and advanced fibrosis categories. Multivariable‐adjusted linear regression models estimated effect sizes, with 95% confidence intervals (CIs), of the presence of liver disease on TL. Cox regression models evaluated associations between TL and all‐cause mortality risk using adjusted hazard ratios (HRs). The cohort was representative of the US population with mean age 46.1 years and mean TL 5.79 kilobase pairs. No overall association between TL and liver disease was found; however, there was a significant negative association of TL and advanced liver fibrosis in individuals aged 65 and above. The liver disease cohort (HR 1.22, 95% CI 0.99‐1.51) and those with metabolic syndrome (HR 1.26, 95% CI 0.96‐1.67) had increased mortality risk with shorter TL. The relationship between TL and all‐cause mortality was stronger in women (HR 1.51, 95% CI 1.02‐2.23) and in non‐Hispanic Whites (HR 1.37, 95% CI 1.02‐1.84). Conclusion: Shortened leukocyte TL is independently associated with advanced liver disease at older ages, and with a higher risk of all‐cause mortality in those with liver disease. These associations reaffirm the need to better understand the role of telomeres in the progression of liver disease. Abstract : We examined the association of peripheral telomere length with liver disease and assessed its impact on mortality using data from the National Health and Nutrition Examination Survey (NHANES). We discovered that shortened leukocyte telomere length is independently associated with advanced liver disease at older ages, and also with a higher risk of all‐cause mortality in those with liver disease.